Dominance hierarchy in colonies of Belonogaster juncea juncea (Vespidae: Polistinae) - Tindo, M.; Dejean, A. (2000)
Dominance behaviours and the structure of the dominance hierarchy in colonies of Belonogaster juncea juncea are described. The frequency of these behaviours was recorded for each individual by noting "all occurrences of rare behaviours". Among the dominance behaviours recorded, the most frequent was "grappling," which represents 69.8 % of the total number of dominance interactions observed. The overall frequency of dominance behaviours was 0.4 ± 0.36 and 2.99 ± 1.97 per hour per individual in pre- and post-emergence colonies, respectively. The data were submitted to the Appleby test, which shows the hierarchy's highly significant level of linearity. The a female showed the highest frequency of dominance interactions and initiated 81.5 % and 48.8 % of the total dominance interactions observed in pre- and post-emergence colonies, respectively. A weekly record of the frequency of dominance interactions throughout the biological cycle shows that this frequency was highest before or immediately after the disappearance of the dominant female. The most aggressive dominance behaviour (falling fights) was observed only during the weeks after the dominant's departure. This behaviour is thus involved in the establishment of the hierarchy and not in its maintenance, which is accomplished by means of less aggressive behaviours.